Tribology for energy conservation / Proceedings of the 24th Leeds-Lyon Symposium on Tribology, held in the Imperial College of Science, Technology and Medicine, London, UK 4th-6th September 1997 /: Proceedings of the 24th Leeds-Lyon Symposium on Tribology, held in the Imperial College of Science, Technology and Medicine, London, UK 4th-6th September 1997. ([date of publication not identified]) - Unknown
No abstract available